PENGARUH LATIHAN PLYOMETRIC TERHADAP KEMAMPUAN AKURASI LONG PASSING PADA SISWA EKSTRAKULIKULER SEPAK BOLA MIT AL ASROR SEKAMPUNG - Gani Saputra; Joan Siswoyo; Suwarli; Fransiskus Nurseto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of plyometric training on the accuracy of long passing among students participating in the soccer extracurricular program at MIT Al Asror Sekampung. The research method employed was a quasi-experimental design. The sample consisted of 30 students selected using the Ordinal Pairing technique. The instrument used in this study was the Move Ball Long Pass Test. The results of the study showed that: (1) there was a significant effect of plyometric training on long passing accuracy (t-value = 29.786 > t-table = 2.145); (2) there was no significant effect in the control group on long passing accuracy (t-value = 1.647 < t-table = 2.145); and (3) there was a significant difference between the treatment group and the control group in terms of long passing accuracy (t-value = 3.569 > t-table = 2.048).